A framework for conceptualizing how narratives from health-care consumers might improve or impede the use of information about provider quality - Melissa Finucane (The Beryl Institute, 2018)
Consumers choosing a health-care provider have access to diverse information including narratives by patients about their prior experiences. However, little research has examined how narratives might improve or impede the use of information about the quality of providers’ performance. This paper describes a conceptual framework for examining mechanisms by which narrative information might influence consumer judgments and decisions about providers. We conducted a conceptual review of risk communication and behavioral decision research. We synthesized the literature to form the foundation of a conceptual framework for assessing how narrative information about provider quality impacts consumer decisions about providers. We identified four key characteristics of narratives (convey emotion; explain logic; provide relational information; and capture naturalistic experience) that may address four consumer needs (avoid surprise and regret; recognize dominant options; motivate to act or not act; and make multi-attribute tradeoff decisions). We also identified three main functions of narratives (provide a simple, powerful cue; imbue quality information with meaning; and stimulate cognition and behavior) in four decision contexts (short-term treatments; external disruptions; chronic illness; problematic experiences). A rigorous research program can be derived from the conceptual framework to generate evidence-based recommendations about whether and how patient narratives might encourage: (1) more reasoned decisions; (2) consistency with a patient’s own values/preferences; and (3) engagement with provider quality information. Research results can be used then to develop robust guidance for health communicators reporting diverse and often incommensurate performance metrics.